Pembuatan Perontok Jagung Berdiameter 200x600 mm dengan 48 Tonjolan untuk Kapasitas 100 kg/Jam - Syamsul Hadi; Amiruddin Abdullah; Yohanes Benediktus Yokasing; Adi Susanto; Agustinus Deka Betan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
The problems faced in threshing corn kernels from the cob are still done manually which requires a lot of energy and time. The purpose of making a corn thresher is to obtain lower energy and time requirements for threshing corn kernels. The method of making a corn thresher includes: protrusion design from an M6 L-key bolt measuring 10×25 mm with a strength of 370 MPa, installation of a 19 mm protrusion position in a spiral at an angle of 45o through a bolt thread on a threshing rotor with a diameter of 200 mm and a length of 600 mm with a total of 48 protrusions, making threshing device components with an angle of 15o, assembling components, testing the device at a rotor speed of 700 rpm from a motor speed of 1400 rpm which is reduced by a V belt and Pulley for hybrid corn variety Nusa-01 with a maximum water content of 14%, a corn fruit diameter of about 50 mm and a length of about 20 cm, evaluation of the device and threshing results. The result of making corn thresher is a cylindrical protrusion from an M6 L-key bolt measuring 10×25 mm with a strength of 370 MPa, the position of the 19 mm protrusion is spirally angled at 45o through the bolt thread on the thresher rotor with a diameter of 200 mm and a length of 600 mm, the number of protrusions is 48 pieces, the production cost is IDR 212,000, the duration of the production process is 240 minutes/unit which implies that corn can be threshed with corn kernel destruction of less than 7%.